Effects of SGLT2 inhibitors on fractures and bone mineral density in type 2 diabetes: An updated meta‐analysis. Issue 7 (15th May 2019) - Li, Xiaoyu; Li, Ting; Cheng, Ying; Lu, Yunhong; Xue, Mei; Xu, Linxin; Liu, Xiangyang; Yu, Xiaochen; Sun, Bei; Chen, Liming
Abstract: Background: The aim of the study is to update and determine the effects of sodium glucose cotransporter 2 (SGLT2) inhibitor therapy on fracture and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM). Methods: We identified 27 eligible randomized controlled trials (RCTs) that compared the efficacy and safety of SGLT2 inhibitors to a placebo in 20 895 T2DM participants, with an average duration of 64.22 weeks. The relative risk (RR) of bone fracture and weighted mean difference (WMD) of changes in the BMD from baseline were determined to evaluate the risk of fracture. The degree of heterogeneity was evaluated by the I 2 statistic, and publication bias was estimated using a funnel plot and Egger test. Results: The pooled RR was 1.02 (95% CI [0.81, 1.28]) with low heterogeneity, indicating that SGLT2 inhibitor treatment was not correlated with a higher risk of fracture. Additionally, no increased risk was found for patients with different ages, sexes, and levels of HbA1c and some biochemical indicators. Three trials with 1303 patients reported a change in the BMD from baseline. SGLT2 inhibitor treatment did not decrease the BMD at four skeletal sites (lumbar spine, femoral neck, total hip, and distal forearm), and the overall WMD was 0.08 (95% CI [−0.09, 0.26]). No significant publication bias was detected. Conclusions: No increased risk for bone fracture was detected in patients with T2DM treated with SGLT2 inhibitors in this meta‐analysis. SGLT2 inhibitor therapy did not appear to affect bone health, but more long‐term detailed data are needed to validate this conclusion.